(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article states that effective logistics management is critical to ensure smooth vehicle service. Learn how to optimize your processes, manage inventory, and track customer demands. As well as logistics management for auto repair shops, logistics and service requirements, inventory management and inventory control and technology in auto repair shops.